Implementasi Management Bandwidth pada Sistem Biling Kafe Menggunakan Autentikasi QR Code - Afifatur Rodiyah (Politeknik Negeri Malang, 2018)
Seeing the high demand for internet, this research will design an implementation of bandwidth management using a user manager, which will be applied to the billing system in public places with internet services. This aims to regulate the bandwidth or internet bandwidth that will be used by each customer in accordance with the total payment. This implementation utilizes a QR Code which will be used as authentication. This QR Code will be printed on the customer's payment receipt / receipt and will be scanned through the application installed on the android mobile phone. The application will be connected to a server which will later connect the customer's smartphone to connect to the internet service. After making the application, it is tested to check the accuracy of the bandwidth received by the customer. From the bandwidth accuracy testing, the results show that the delivery of bandwidth to the customer has an error with an average error in the download bandwidth of 6.5% and the upload bandwidth of 17%. The occurrence of this error is due to the ping and jitter values ??during data transmission, with an average ping of 78.7 ms and a jitter of 82.7 ms. Whereas in reading the QR Code, it was found that when using a camera with a 5MP resolution the QR Code can be read up to a distance of 90 cm and when using a camera with a resolution of 20.7MP, the QR Code can be read up to a distance of 110 cm.